PENGARUH MODEL STAD TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MATERI FPB DAN KPK BAGI SISWA KELAS IV SD NEGERI 43 PANGKALPINANG - Nurwawa; Ayen Arsisari; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2023)
This study was motivated by the lack of understanding of students' mathematical concepts on the material of FPB and KPK. Students tend to find it difficult to understand material that has been previously learned. This study aims to determine the effect of. The effect of STAD Model on Understanding Mathematical Concepts of GCD and KPK. This research uses quantitative research methods. The method used is Pre-Experimental Design with One Group Pretest-Posttest Design. The data collection technique in this study was a written test. The sample in this study used the Saturated Sampling technique. This method was chosen based on consideration of the variables to be studied, namely the understanding of students' mathematical concepts. The research sample was fourth grade students of SD Negeri 43 Pangkalpinang as many as 25 students. The data analysis technique used the t test given to class IV to determine the effect of the STAD model on students' understanding of mathematical concepts. The understanding of mathematical concepts studied is cognitive in the form of questions. The results of this study using the t test are the value of tcount = 7.865> table = 1.711 then Ha is accepted. So it can be concluded that there is an influence of the STAD model on understanding the concept of mathematics FPB and KPK material in class IV SD Negeri 43 Pangkalpinang.